Diet quality and anthropometric indices of patients undergone bariatric surgery: the prospective Tehran obesity treatment study - Firoozeh Hosseini-Esfahani; Mona Kazemi-Aliakbar; Glareh koochakpoor; Maryam Barzin; Alireza Khalaj; Majid Valizadeh; Parvin Mirmiran (BMC Surgery, 2023)
Abstract Background Patients undergone bariatric surgery (BS) has long-term risks including decrease in diet quality, nutritional deficiencies and weight regain. This study focus on assessing dietary quality and food group components in patients one year after BS, the relationship between dietary quality score and anthropometric indices, and also evaluating the trend of body mass index (BMI) of these patients three years after BS. Methods A total of 160 obese patients (BMI ≥ 35 kg/m2) were undergone sleeve gastrectomy (SG) (n = 108) or gastric bypass (GB) (n = 52), participated in this study. They were assessed for dietary intakes using three 24-hour dietary recalls one year after surgery. Dietary quality was assessed using food pyramid for post BS patients and healthy eating index (HEI). Anthropometric measurements were taken pre-surgery and 1, 2 and 3 years after operation. Results The mean age of patients was 39.9 ± 11 years (79% female). The mean ± SD percentage of excess weight loss was 76.6 ± 21.0 one year after surgery. Intake patterns are generally (up to 60%) not consistent with the food pyramid. The mean total HEI score was 64 ± 12 out of 100. More than %60 of participants is exceeding the recommendations for saturated fat and sodium. The HEI score did not show significant relationship with anthropometric indices. The mean of BMI in SG group increased over three years of follow up, while in GB group, there were no significant differences in BMI during three years of follow up. Conclusions These findings showed that patients had not healthy pattern intake one year after BS. Diet quality did not show significant relationship with anthropometric indices. The trend of BMI three years after surgery was different based on surgery types.